Association of Interferon-Alpha and Ribavirin-Induced Thyroid Dysfunction with Severity of Disease and Response to Treatment in Pakistani Asian Patients of Chronic Hepatitis C. (2nd September 2012) - Nadeem, Amina; Aslam, Muhammad
Abstract : Objective . To determine the association of thyroid dysfunction with the severity of the disease and response to treatment in patients of chronic hepatitis C. Design . Cohort study. Patients . One hundred and sixty seven noncirrhotic chronic hepatitis C patients were grouped into treatment group (n = 107 ) and control group (n = 60 ). Measurements . Baseline S. ALT and S. AST by IFCC and S. TSH, S. free T4, and S.T3 level were measured by chemiluminescence method. The severity of the disease was measured by Knodell histopathological index (HPI) on liver biopsy. Study group patients underwent 24-weeks IFN and ribavirin therapy and thyroid functions were determined at weeks 0, 12, and 24. Response to therapy was determined by PCR-HCV test. Results . 20 treated patients (18.69%) developed thyroid dysfunction with relative risk (RR) of 11.25 and attributable risk (AR) of 91%. Females were at higher risk. Hypothyroidism was common than hyperthyroidism. There was no significant association between thyroid dysfunction and severity of the disease (P = 0.81 ) and response to therapy (P = 0.79 ). Conclusion . Interferon-alpha and ribavirin therapy induces thyroid dysfunction in chronic hepatitis C patients. There is no association between severity of disease and response to therapy with interferon-induced thyroid dysfunction.